Moderate dose of hydroxyurea in children with sickle cell disease and stroke. Preliminary results. - Machín-García, Sergio; Menéndez Veitía, Andrea; Sherle Matamoros, Claudio; Svarch, Eva; Arencibia Núñez, Alberto; Gutíerrez Díaz, Adys; García Peralta, Tania; Lam Díaz, Rosa (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Twenty children with sickle cell anemia, two with SC hemoglobinopathy and one with S/β0 thalassemia were treated, with a previous stroke or abnormal ultrasound transcranial Doppler (TCD) flow velocities more than 170 cm/s. The mean follow-up was of 41 ± 19 months. Hydroxyurea (HU) at a dose of 25 mg/kg/day associated with chronic transfusion therapy, was administrated during one year to patients with stroke. Patients with abnormal TCD received only HU at the same dose. There was a significant decrease of stroke (p <0.02) and TCD flow velocities in the right middle cerebral artery (p <0.003). It was necessary to associate chronic transfusion therapy in three children with high velocities in TCD without stroke, due to the lack of response to the treatment with HU. The combination of HU and transfusions during one year can be useful for stroke therapy and prevention.